Should investors jump into the bandwagon? The case of FGVH'S IPO - Abdul Rahim, Ruzita; Yaacob, Mohd Hasimi (2015)
It was 8:29am on Thursday 31st May 2012 but the meeting room at Hijrah Investment Consultancy House (HICH) was already packed with all members of Helix Research unit, one of the six units in the firm consisting of five securities analysts specializing on equity securities and responsible for advising the firm’s high-worth clients. Scattered on the round table were prospectuses of Felda Global Venture Holdings (FGVH) which were still warm for just being delivered from the printing room.On the white board, the Chief Operating Officer (COO) Dato’ Badruzaman’s handwriting “keep our clients happy or die trying” from his briefing yesterday, was still untouched. Barely three years competing in the industry, HICH had secured quite a number of big accounts. However, competition in the industry was getting stiffer due to entrance of new securities houses.When Afiq Firash, Head of Helix Research unit, announced to his team members the withdrawal of two big accounts worth a total wealth of RM3.5 million right after his meeting with the COO, they were disappointed but not completely shocked by the news either. “We have to be extra detail in our estimation … they (the clients) need to be convinced or else they will walk away with their dollars”.That was Afiq Firash’s last word before leaving the team with an instruction to “treat the accounts like your own” and reminding the team that initial public offering (IPO) of FGVH was the project that would test Helix’s ability to deliver.